Volume 2: Structures, Safety and Reliability 2008
DOI: 10.1115/omae2008-57583
|View full text |Cite
|
Sign up to set email alerts
|

Tapering Effects on the Installation of Suction Caissons in Clay

Abstract: This paper reports results from an investigation on the tapering effects on the installation and pull-out performance of suction caissons. A numerical finite element approach has been used for the study. The finite element models have first been calibrated/verified against several available experimental data for the installation of the upright suction caissons in clay. The verified models have then been used to examine the behaviour of the tapered suction caissons during the pull-out and installation phases. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…has already been investigated by a number of researchers (Bang et al 2000;Cassidy et al 2006;Narasimha Rao et al 2006;Zeinoddini et al 2010). Some previous numerical investigations indicated that positively tapered suction caissons may provide pull-out capacities considerably higher than that of their equivalent upright caissons Zeinoddini et al 2008a;Zeinoddini et al 2008b;Zeinoddini, Hobbi, et al 2009;Zeinoddini, Keyvani, et al 2009). A thorough evaluation of the performance of tapered suction caissons requires further studies, particularly, experimental investigations.…”
Section: Introductionmentioning
confidence: 94%
“…has already been investigated by a number of researchers (Bang et al 2000;Cassidy et al 2006;Narasimha Rao et al 2006;Zeinoddini et al 2010). Some previous numerical investigations indicated that positively tapered suction caissons may provide pull-out capacities considerably higher than that of their equivalent upright caissons Zeinoddini et al 2008a;Zeinoddini et al 2008b;Zeinoddini, Hobbi, et al 2009;Zeinoddini, Keyvani, et al 2009). A thorough evaluation of the performance of tapered suction caissons requires further studies, particularly, experimental investigations.…”
Section: Introductionmentioning
confidence: 94%